Natural infection of hybrid sturgeon (Acipenser baerii♀×Acipenser schrenckii♂) with Nocardia seriolae and white sturgeon iridovirus: pathological and transcriptomic analyses - Ni, Luyun; Li, Pengcheng; Zou, Qiaolin; Li, Feiyang; Chen, Yeyu; Chen, Haoting; Lai, Jiansheng; Du, Jun; Liu, Ya (Frontiers in Immunology, 2024)
IntroductionIn August 2023, hybrid sturgeons (Acipenser baerii♀×Acipenser schrenckii♂) cultured in Sichuan, China, showed infectious disease symptoms, including ulcers, liver and spleen nodules, and high mortality rates.MethodsPathogenic bacteria were isolated from the liver of diseased sturgeons and analyzed for their phenotypic and molecular traits. Furthermore, iridovirus-specific TaqMan real-time PCR (RT-PCR) analyses were conducted. The histopathological characteristics were analyzed using paraffin sectioning and transmission electron microscopy (TEM). Transcriptome sequencing was performed to elucidate the impact of pathogen exposure and immune response profiles in infected sturgeon.ResultsPathogenic bacteria isolation and phylogenetic analyses of the 16S rRNA gene confirmed that the isolated bacteria clustered within the Nocardia seriolae group. The TaqMan RT-PCR assay was performed to detect the presence of white sturgeon iridovirus (WSIV), indicating a weakly positive signal. Histopathological examination revealed severe damage to various tissues, and a notable presence of bacteria was observed through acid-fast staining. Transmission electron microscopy analysis showed the presence of abundant bacteria and virus particles, indicating cellular invasion and subsequent damage. In summary, the disease in hybrid sturgeons was diagnosed as infection of N. seriolae and WSIV. To investigate the immune response of hybrid sturgeons to this infection, spleen transcriptomes were analyzed. Numerous immune-related genes and pathways, including the “Toll-like receptor”, “B-cell receptor”, and “T-cell receptor” signaling pathways, were altered in response to pathogenic threats. Significantly downregulated of key components of TCR and BCR signaling pathways, such as ZAP70, BTK, and CD79A, suggested a temporary inhibition of these pathways critical for cellular immunity post-infection. Gene set enrichment analysis revealed significant suppression of the apoptosis signaling pathway and activation of autophagy and mitophagy signaling pathways following infection. Specifically, in the death receptor-mediated apoptosis signaling pathway, downregulation of TNFα, TRAIL, CASP6, and CASP8 was observed, while several genes in the autophagy and mitophagy pathways showed upregulated expression post-infection.DiscussionWe report the initial occurrence of N. seriolae infection in cultured sturgeons. These findings could provide a theoretical basis for diagnosing and preventing this disease, as well as enhance the understanding of host-pathogen interactions in fish.